Exploring student-centered instructions in English as a foreign language (EFL) learning in Indonesia through trioethnographic reflections - Wungu, Ratu Nur Rozi Sekar; Nisa, Meilinda Choirun; Firdaus, Muhammad Hanif Ali; Syaripudin, Usep; Erawati, Turini (Asatiza: Jurnal Pendidikan, 2024)
This article examines professional development through the lens of trioethnographic reflections to enhance student-centered teaching practices. Trioethnography, derived from duoethnography, is a qualitative research method where two or more researchers engage in reflective dialogue to explore an issue. We collected data through four reflective conversations, guided by faculty advisors, during our teaching practicum. Our analysis identified three key themes from these dialogues: (1) reexamining our beliefs about student-centered instruction, (2) recognizing sociocultural barriers to this approach, and (3) sharing experiences of relearning teaching methods. These conversations created a safe space to exchange insights and collaboratively build understanding. The findings have significant implications for teachers and teacher education. First, teachers must continually reassess the beliefs and assumptions that underpin their teaching. Second, understanding students more deeply is crucial for effectively implementing student-centered teaching, especially in EFL contexts. Third, preservice teacher education should emphasize the importance of self-reflection and critical examination of teaching beliefs, fostering both personal and professional growth. Lastly, future research should narrow its focus on specific practical issues within student-centered EFL teaching to further enrich the field and improve teaching practices. Collaborative reflection should become a routine part of teacher education programs to better prepare future educators.